Bank concentration and non-performing loans in Central and Eastern European countries - Çifter, Atilla (Journal of Business Economics and Management, 2014)
This paper examines the effect of bank concentration on the non-performing loans (NPLs) for ten Central and Eastern European (CEE) countries. The short-run effect of bank concentration is tested with the generalised method of moments system and the instrumental variable approaches, and the long-run effect is tested with the fully modified ordinary least square (FMOLS) approach. The empirical analysis shows that the bank concentration is an insignificant factor on the NPLs, either in the short or in the long-run of the panel data set. On the other hand, individual FMOLS results reveal that the bank concentration reduces the NPLs in Estonia, Latvia, and Slovakia, and increases the NPLs in Bulgaria, Croatia, Lithuania, Poland, and Slovenia in the long-run. According to this evidence, the bank concentration does not reduce the credit risk for all of the CEE countries. Therefore, bank concentration may not affect systemic stability in the CEE countries. These findings are also robust in controlling several factors, including additional control variables. As a result, the relationship between the bank concentration and the NPLs, in regards to the CEE countries, is ambiguous.